Dimensi Pendidikan Multikultural - Wahdiah Wahdiah; Radjiman Ismail; H. Moh. Natsir Mahmud (Jurnal Ilmiah Wahana Pendidikan, 2023)
Multiculturalism is an ideology that emphasizes equality in cultural differences. Multicultural education recognizes the ethnic and cultural diversity of a nation's people.The research method used is descriptive research with library research. Education that is oriented towards humanity, togetherness and peace to develop the principles of democracy, equality and justice in social life, especially in heterogeneous societies, requires a universal life orientation. Among universal life orientations are humanity, togetherness, and peace. This universal life orientation is an orientation point for multicultural education. Multicultural education is education that provides recognition, appreciation and respect for differences in equality in terms of language, race, ethnicity, culture and religion.